Pendidikan Islam di Era Digital: Respon terhadap Isu Kesetaraan Gender di Media Sosial - Annisa, Annisa; Anggina, Dhea Yuspi; Syahrani, Syalum; Sari, Herlini Puspika (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
The development of digital technology has significantly transformed Islamic education, particularly in the growing discourse on gender equality within digital public spaces. Social media has become a new arena where diverse gender narratives—from progressive to conservative—compete for public attention, requiring a more systematic response from Islamic education. This study aims to describe the foundational concepts of gender in Islamic education, analyze how social media shapes gender perceptions among Muslim communities, and formulate effective educational strategies for responding to these challenges in the digital era. Using a library research design with a descriptive qualitative approach, this study applies thematic content analysis to synthesize relevant academic literature. The findings indicate that Islamic education holds strong potential to promote gender justice through theological, pedagogical, and digital literacy approaches. Nevertheless, significant challenges persist, including biased interpretations, the spread of misinformation, and the dominance of patriarchal narratives in online spaces. The study’s implications highlight the need for curriculum reform grounded in gender equality, teacher capacity development, strengthened Islamic digital literacy, and collaborative efforts among educators, scholars, and digital communities to build a more inclusive and moderate digital da'wah environment. These findings are expected to serve as a foundation for developing adaptive Islamic educational strategies that respond effectively to gender dynamics in the cyber era.